Nationwide Study to Assess the Psychosocial, Financial, and Professional Impact of COVID-19 Pandemic on Radiation Therapy Technologists - Rohit Vadgaonkar (JCO Global Oncology, 2022)
PURPOSERadiation therapy technologists (RTTs), being the frontline health care workers, are vulnerable to COVID-19 disease and subsequent detrimental consequences of the pandemic. Hence, the study was undertaken for the comprehensive assessment of adverse effects of COVID-19 pandemic on RTTs.MATERIALS AND METHODSThis cross-sectional, survey-based study was carried out among RTTs working in various cancer centers across India. Assessment was carried out by using a questionnaire comprising the demographic profile and a structured instrument to quantify psychological, social, financial, and professional impact of COVID-19 pandemic. Responses were collected between February 1, 2021, and April 31, 2021.RESULTSOf 302 responders, more than two third of the RTTs were concerned for getting COVID-19 disease either outside the hospital (n = 210, 69.5%) or from patients or attendants (n = 220, 72.8%). More than one third of RTTs were very much concerned for increased financial burden of COVID-19 pandemic (n = 94, 34.1%), and one third (n = 92, 30.5%) were very much concerned for newly imposed restrictions. RTTs working in a private setup (P = .000), living in a tier 1 city (P = .028), and lacking the coverage of COVID-19 disease in health insurance (P = .010) faced a significantly higher financial burden. RTTs living in tier 1 city (P = .023) and those who were in profession for > 5 years (P = .013) had significantly higher concern for ensuring proper sanitization of the professional environment. More than half (n = 171, 56.6%) were interested in taking COVID-19 vaccine.CONCLUSIONCOVID-19 pandemic adversely affected psychosocial, financial, and professional well-being of RTTs even after subsidizing the initial wave, and a timely intervention is warranted for their well-being and to sustain oncologic facilities.